Preservation of Fat-free Mass after Bariatric Surgery: A Comparison of Malabsorptive and Restrictive Procedures. Issue 8 (August 2015) - Wells, Jason; Miller, Megan; Perry, Brittonni; Ewing, Joseph A.; Hale, Allyson L.; Scott, John D.
The Roux-en-Y gastric bypass (RYGB) has been shown to cause significant weight loss. However, fat-free mass (FFM) is often lost with this rapid weight change. It is suggested that the loss of FFM is minimized with restrictive-only procedures, such as the vertical sleeve gastrectomy (VSG), when compared with malabsorptive surgery. The purpose of the study was to determine the difference in the postoperative loss of FFM between RYBG and VSG patients. We reviewed all patients who underwent RYGB or VSG between May 2012 and January 2013. Patients were evaluated one month before their procedure and 12 months after for comparison of results. Preoperative and postoperative body analysis data were procured using a body composition analysis device. Within the study period, 33 patients underwent a RYGB procedure and 20 patients a VSG. After 12 months, RYGB patients had an average increase of 38.15 per cent in their proportion of FFM, whereas VSG patients had an average FFM increase of 22.09 per cent, a statically significant difference ( P = 0.004). The RYGB helps preserve overall FFM as compared with the VSG. These findings are unexpected because malabsorptive procedures require increased protein intake, resulting in a stronger likelihood of inadequate protein intake, which may lead to protein malnutrition.